Long-Term Treatment with Bulevirtide in Patients with Chronic Hepatitis D and Advanced Chronic Liver Disease - Ayaz Sapuk; Leonie Steinhoff; Kristin Hünninghaus; Katharina Willuweit; Jassin Rashidi Alavijeh; Benedikt Hild; Lucia Asar; Hartmut H. Schmidt; Christoph Schramm (Canadian Journal of Gastroenterology and Hepatology)
Bulevirtide (BLV) is approved for the treatment of chronic hepatitis D (CHD). Because only limited long-term experience has been reported, we aimed to evaluate the efficacy and safety of BLV treatment in patients with advanced chronic liver disease (ACLD). We performed a retrospective analysis of patients with CHD who received BLV 2 mg/day for >12 months at a tertiary center. Virological response (VR) was defined as a reduction in hepatitis delta virus-ribonucleic acid (HDV-RNA) ≥2 log10 from baseline or HDV-RNA negativity and biochemical response (BR) as gender-specific normalization of transaminases. We identified 14 patients (9 men, 5 women; median age of 48 years; interquartile range (IQR) of 37–55), of whom 12 (86%) had suggested or assumed ACLD according to Baveno VI criteria. The median duration of BLV treatment was 26 months (IQR 17–27). During treatment, the mean HDV-RNA level decreased from log10 5.58 IU/ml to levels between log10 2.19 IU/ml and log10 3.19 IU/ml. HDV-RNA negativity was achieved in up to 63% after 24 months. VR and BR were 86% and 43% after 12 months, 90% and 60% after 18 months, 75% and 75% after 24 months, and 100% and 50% after 30 months, respectively. Two nonpersisting viral breakthroughs were observed after 24 months of treatment. The Child Pugh score and model of end-stage liver disease (MELD) scores remained stable or improved in 12 patients (86%). Only one patient developed hepatic decompensation after 24 months of treatment with ascites requiring large-volume paracentesis which was not associated with viral breakthrough, portal vein thrombosis, or hepatocellular carcinoma. Treatment with BLV beyond one year is effective and safe for patients with CHD and ACLD. Liver function remained stable or improved during treatment in the vast majority of patients, and only one case of hepatic decompensation occurred during a median follow-up of 26 months.